Phenotypic selection by kelp gulls against pear-shaped shells of the Antarctic limpet Nacella concinna - Castillo, Santiago; de Aranzamendi, Maria Carla; Martínez, Juan Jos; Sahade, Ricardo Jose (Biological Journal of the Linnean Society)
The Antarctic limpet (Nacella concinna) presents two ecotypes related to different water depths: littoral individuals have a robust and taller shell while sublittoral individuals are thinner and flatter. Among the environmental factors possibly causing this divergence, avian predation upon littoral individuals has been mooted but has received little research attention. The kelp gull (Larus dominicanus) is the principal consumer of littoral limpets in the study area. We used shells from littoral and sublittoral zones, and from gull middens to examine - through linear morphometrics and elliptic Fourier analysis - whether selective predation exists, and to evaluate the mode of selection that could be operating on different traits. We found that limpet individuals with the apex displaced towards the anterior side were more likely to be predated. However, a remarkable result was that gulls select dorsal pear-shaped rather than elliptical shells and that there is a directional selection against pear-shaped limpets. However, in contrast to previous studies, we did not find that the proportions of elliptical or pear-shaped individuals differed between the littoral and sublittoral zones. This discrepancy could be related to variations in predatory intensity in different locations. These results suggest that where gulls have a strong influence, their effect could be a key factor in dorsal differentiation in limpet shells. Fil: Castillo, Santiago. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: de Aranzamendi, Maria Carla. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto ...